Analysis of the book Judo: path of medals, by Alexandre Velly Nunes (Revista de Artes Marciales Asiáticas, 2020)
This review presents the book Judô: caminho das medalhas, written by PhD Professor Alexandre Velly Nunes, published in Brazilian Portuguese in 2013 by Kazuá. This work comes from the doctoral research of the author, who interviewed about 90 personages from the history of Brazilian judo in four years of studies. The objective was to present the origins of this sport in the country based on the oral history of the life of Brazilian athletes, who were medalists in World Championships and Olympic Games, and their sensei. I make a brief presentation of the author and summarize the contents of the book, followed by my comments and conclusion.